Overview of knowledge management in the public sector - Hui Yuen, Yum ([s.n.] [S.l.], 2007)
Presents an overview of knowledge management (KM) initiatives and trends in the public sector from primarily developing countries. Includes recommendations for successful KM implementations, by drawing from lessons learned and best practices in published reports of successful public sector KM initiatives.